One-dimensional photonic crystal structure enhanced external-magnetic-field-free spintronic terahertz high-field emitter - Zehao Yang; Jiahui Li; Shaojie Liu; Zejun Ren; Mingxuan Zhang; Chunyan Geng; Xiufeng Han; Caihua Wan; Xiaojun Wu (Science and Technology of Advanced Materials)
Intense terahertz (THz) radiation in free space offers multifaceted capabilities for accelerating electron, understanding the mesoscale architecture in (bio)materials, elementary excitation and so on. Recently popularized spintronic THz emitters (STEs) with their versatility such as ultra-broadband, large-size and ease-for-integration have become one of the most promising alternative for the next generation of intense THz sources. Nevertheless, the typical W | Co[Formula: see text]Fe[Formula: see text]B[Formula: see text] | Pt necessitates an external-magnetic-field to saturate magnetization for stable operation, limiting its scalability for achieving higher THz field with uniform distribution over larger sample areas. Here we demonstrate the methodologies of enhancing the high-field THz radiation of external-magnetic-field-free IrMn[Formula: see text] | Co[Formula: see text]Fe[Formula: see text]B[Formula: see text] | W trilayer heterostructure via optimizing the substrate with superior thermal conductivity and integrating a one-dimensional photonic crystal (PC) structure to maximize the radiation efficiency. Under the excitation of a 1 kHz Ti: sapphire femtosecond laser amplifier with central wavelength of 800 nm, pulse duration of 35 fs, and maximum single pulse energy of 5.5 mJ, we successfully generate intense THz radiation with focal peak electric field up to 650 kV/cm with frequency range covering 0.1–5.5 THz from MgO-coated sample without external-magnetic-fields. These high-field STEs will also enable other applications such as ultra-broadband high-field THz spectroscopy and polarization-based large-size strong-field THz imaging.